From the Love of God to the God-Love: Reflections on an Unamunian Problem - Molina, Antonio M. López (Pensamiento. Revista de Investigación e Información Filosófica, 2014)
The central thesis of this paper is as follows: Unamuno’s genuine concept of God, namely,the biotic God, the cordial God, the God-Love, is the result of the convergence of three philosophical traditions in which Unamuno introduces a peculiar change. The first is Unamuno’s critique of ScholasticTheology and its conception of God as ens realissimum, First Cause or Prime Mover. The second can be found in the Augustinian-Lutheran-Kierkegaardian tradition and its call to the inner world, personality and individuality. And finally, engaging in a peculiar reflection activity that allows him to join the intellectualist and voluntarist traditions, the philosopher of Salamanca turns to the atheistic philosophy of Schopenhauer,who presents a world as will, pain and compassion. A new conception of God based on will, faith and hope emerges because of the critique and transformation of these philosophies.
Keywords: Unamuno; God; Faith; Will; Theology